Association of glucose-6-phosphate dehydrogenase activity with oocyte cytoplasmic lipid content, developmental competence, and expression of candidate genes in a sheep model - Mohammadi-Sangcheshmeh, Abdollah (Springer US, 2014)
PURPOSE: To evaluate associations of glucose-6-phosphate dehydrogenase (G6PDH) activity in sheep oocytes with cytoplasmic lipid content, maturational competence, developmental competence to the blastocyst stage, and gene expression of certain molecular markers. METHODS: Before brilliant cresyl blue (BCB) staining test, oocytes were classified as high, middle, and low cytoplasmic lipid content (HCLC, MCLC, and LCLC) and after the test as having low or high G6PDH-activity (BCB(+) and BCB(−), respectively). After maturation in vitro, a group of oocytes were subjected to IVF followed by in vitro embryo culture and another group was used for evaluation of expression of candidate genes. RESULTS: The cleavage and blastosyst rates were lowest (P < 0.05) in LCLC group, intermediate (P < 0.05) in MCLC group and highest (P < 0.05) in HCLC group. More (P < 0.05) oocytes in HCLC group were BCB(+), and higher (P < 0.05) maturation, cleavage, and blastocyst rates were seen for BCB(+) oocytes than the BCB(−) oocytes. Our gene expression data indicated that mRNA transcript abundance of ITGB2, pZP3, BMP15, and GDF9 genes was similar between BCB oocytes groups. However, the expression of ATP1A1 was higher (P < 0.05) for BCB(+) oocytes compared to BCB(−) oocytes. In addition, BAX transcript abundance was similar (P > 0.05) among BCB(+), BCB(−), and control groups, before and after maturation in vitro. CONCLUSION: Activity of G6PDH in sheep oocytes is highly associated with lipid content, and compared with the morphological parameters might be a more precise and objective predictor for subsequent developmental competence in vitro.